IMPROVING THE METHODOLOGY OF DEVELOPING TECHNICAL THINKING IN TEACHING PHYSICS IN ACADEMIC LYCEUMS (Conferencea, 2023)
In the article, it is important to plan practical exercises in physics, including problem solving, for academic lyceums, especially by solving technical problems, future military specialists can gain knowledge and skills in the technical direction, and it is a methodical way of forming their competence in their fields. are discussed.